Relationship between Social Support and Instrumental Activities of Daily Living among Older Adults in Assiut City - Hanan Abd Allah Abozeid,; Shimaa Hassan Abd el Fatah,; Shimaa Abdelrehim Khalaf, (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2018)
Background: Social support provides the older adults with the opportunity to proper physical function which help preserve their functional abilities. Aim: To examine the relationships between social support of older adults with their demographic characteristics, presence of comorbidities and IADL in Assiut city.  Setting and Subjects: The study was conducted in the three geriatric clubs which present in Assiut City and outpatient clinics of chronic diseases at the main Assuit university hospital, subjects of 178 older adults selected from the previous areas (a convenient sample of 68 older adults from outpatient clinics and 110 from the three geriatric clubs).  Tools: Three tools were utilized for data collection: Tool I: Part (I): the baseline demographic information, Part (II):  Social support questionnaire tool and Tool (III): The Lawton Instrumental Activities of Daily Living (IADL) Scale.   Results: half of the outpatient sample (50%) had moderate social support and the other half had poor social support level, More than half of both groups (29%) had moderate level of comorbidity, some of geriatric clubs sample (5.5%) were dependent in IADL and that percent raised to (20.6%) in outpatient clinics sample.  Conclusion: Older adults who attended geriatric clubs that they participate routinely in social contacts and activities had a strong social support and decreased level of IADL dependency. Increased dependency of Instrumental Activities of Daily Living (IADL) among outpatient clinics sample. There were statistical significant differences regarding social support scores and age, sex, educational level and residence of both the studied samples.  Recommendation: Development of policies to address the point of social relations and activities for older adults from formal, informal and institutional network.